THE LGBT COMMUNITY AS A STAKEHOLDER IN COMMUNICATING CORPORATE SOCIAL RESPONSIBILITY: AN ANALYSIS OF SELECTED CASE STUDIES - Szyndlar, Marta; Wąsikiewicz-Firlej, Emilia (Scripta Neophilologica Posnaniensia, 2019)
Corporate Social Responsibility (CSR) has become an indispensable element of corporate communication. Engagement in social initiatives enables companies to stabilise their positive image, present their values and communicate with stakeholders. Although in recent years the LGBT community has more and more frequently been the addressee of such corporate actions, this theme has rarely been explored by scholars. The present paper aims to investigate how corporate initiatives related to CSR are communicated to the LGBT community as one of the corporate stakeholders. Due to the scarcity of subsequent research, the current qualitative study is of an explorative character and has taken the form of a case study. Three brands renown for addressing the LGBT community, i.e. Ben and Jerry’s, Levi’s and Absolut Vodka, have been selected for the study, which analyses the relevant communication practices. The study primarily aims to specify the image of the LBGT community emerging from the campaigns analysed and to identify the communication channels and tools applied. Additionally, it also attempts to scrutinise the outcomes of these activities and their impact on corporate reputation as well as the perception of the LGBT community in a wider social context.